Toni Morrison's fiction - Furman, Jan. (Columbia, South Carolina : The University of South Carolina Press, 2014)
In this revised introduction to Nobel Laureate Toni Morrison's novels, Jan Furman extends and updates her critical commentary. New chapters on four novels following the publication of Jazz in 1992 continue Furman's explorations of Morrison's themes and narrative strategies. In all Furman surveys ten works that include the trilogy novels, a short story, and a book of criticism to identify Morrison's recurrent concern with the destructive tensions that define human experience: the clash of gender and authority, the individual and community, race and national identity, culture and authenticity, and the self and other.
Selected BibliographyIndex; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; V; W; Z.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Morrison, Toni -- Criticism and interpretation; Morrison, Toni -- Criticism and interpretation; Morrison, Toni; Women and literature -- United States -- History -- 20th century; African American women in literature; African Americans in literature; Femmes et littérature -- États-Unis -- Histoire -- 20e siècle.; Noirs américains dans la littérature.; LITERARY CRITICISM -- American -- General; African American women in literature; African Americans in literature; Women and literature; United States; 1900-1999; Criticism, interpretation, etc; History